The Essence of the Synergy of the Strategic Role of the Indonesian National Army (TNI) in Countering Acts of Criminal Acts of Terrorism in Indonesia - Wahid, Amran; Husen, La Ode; Hidjaz, Kamal; Ahmad, Kamri (Journal of Cultural Analysis and Social Change, 2026)
Terrorism remains a persistent and evolving threat to Indonesia, undermining national security, constitutional order, public safety, and humanitarian values. Although the state has strengthened its counter-terrorism framework through Law No. 15/2003 as amended by Law No. 5/2018 and Law No. 34/2004 on the Indonesian National Armed Forces (TNI), recurring incidents indicate that legal instruments alone are insufficient. This study examines the essence of synergy in the strategic role of the TNI in countering terrorism, particularly within the framework of Operations Other Than War and its coordination with the Indonesian National Police (Polri) and the National Counter-Terrorism Agency (BNPT). The research employs a normative–empirical legal design. The normative component analyzes statutory provisions, legal principles, and constitutional doctrines governing counter-terrorism, while the empirical component investigates implementation practices through field observations, interviews, and case analysis in regions with high vulnerability, including Sulawesi. This dual approach reveals a persistent gap between das sollen (the law as it should be) and das sein (the law as implemented). Findings demonstrate that while the TNI possesses a legitimate constitutional mandate to assist in combating terrorism, the absence of clear operational boundaries, activation protocols, and unified command mechanisms often leads to overlapping authority, fragmented coordination, and delays in emergency responses. At the same time, concerns regarding human rights safeguards and civilian oversight persist. The study concludes that an integrated synergy model—grounded in legal certainty, accountability, proportionality, and respect for human rights—is essential to ensure that TNI involvement strengthens, rather than substitutes, civilian law-enforcement functions. Policy reform should prioritize clearer regulations, interoperable coordination mechanisms, and standardized operational guidelines to enhance effectiveness and legitimacy in Indonesia’s counter-terrorism efforts.